ANALYSIS OF THE COMBINED IMPACT OF AROMATIC CARBOHYDRATES AND FORMALDEHYDE ON THE STATION OF THE HEALTH OF THE CHILD POPULATION - Рублевська, Надія; Степанов, Сергій; Ревенко, Світлана; Рибачук, Ганна; Рублевський, Владислав (Modern engineering and innovative technologies, 2022)
According to the results of correlation and regression analysis the relationship between the incidence of children and the combined aerogenic load of phenol, formaldehyde and aromatic hydrocarbons. A prognostic model is proposed to determine the level of